Love in the Balance - Jennings, Regina (Regina Lea) (Bethany House, a division of Baker Publishing Group, 2013)
"Molly Lovelace dreams of being a society leader in 1879 Lockhart, Texas, but being smitten with handsome wrangler Bailey Garner doesn't seem the quickest route. If only he would settle down so he could support a family. Bailey imagines doing great things for God, but his greatest obstacle is Molly. As long as he thought they'd be married, he excused their stolen kisses, but when she keeps refusing, he vows to earn her love. In town, he tries his hand at several different trades, but everywhere he turns he runs into the mysterious stranger Edward Pierrepont. No surprise that Molly's always making calf eyes at the wealthy adventurer. As pressure from Molly's parents grows she is forced into a hasty decision. Had she weighed all her options and will she find love in the balance?"--Amazon.com, viewed February 27, 2013.